Pathways to Gender Equality and Empowerment, Sustainable Animal and Aquatic Foods: Setting the Science Agenda (2025–2030) - Mapedza, Everisto; Adam, Rahma; Galie, Alessandra; Bonis-Profumo, Gianna; Terfa, Zelalem; Njiru, Nelly; Mosbah, Menna; Njogu, Lucy (CGIAR System Organization, 2025)
This Sustainable Animal and Aquatic Foods (SAAF) brief maps out gender entry points for the new Science Program which will run from 2025 to 2030. The brief provides six pathways to enhance gender equality and women’s empowerment in CGIAR Sustainable Animal and Aquatic Foods (SAAF) Science Program. This brief offers Gender Equality and Social Inclusion (GESI) solutions which range from accommodative to transformative through norm changes. While accommodative gender solutions try to provide solutions within existing norms and cultures, in the long term, it is the transformative solutions which change societies for more equitable and inclusive gender outcomes. The brief goes beyond business as usual or gender mainstreaming approaches by setting an ambitious gender research agenda for the SAAF and related science programs. The SAAF science program provides opportunities for women and youth from low-and-middle-income countries (LMICs) to participate, engage and benefit from animal and aquatic food systems (AAFS). Gender and restrictive social norms in AAFS can lead to inequalities. This limits the potential of AAFS to provide avenues for women’s economic and social empowerment and equitable job creation. Addressing barriers towards gender inequality, and youth and women’s empowerment through gender transformative approaches is vital if AAFS are to contribute effectively to improving food security, nutrition and livelihoods, while reducing poverty.